PENGARUH AUDIT TENURE, ROTASI AUDIT DAN UKURAN PERUSAHAAN TERHADAP KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Maria Mercedes Br. Aritonang; Rana Fathinah Ananda; Aditya Amanda Pane (Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The aim of this research is to determine the effect of audit tenure, audit rotation and company size on audit quality in food and beverage sub-sector manufacturing companies listed on the IDX in 2019-2022, partially and simultaneously. The research design used is an associative approach. The population in this study was 88 Food and Beverage Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange for the 2019-2022 period with a sampling technique based on criteria using purposive sampling, namely Food and Beverage Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange in the period 2019-2022 as many as 88 companies. Based on these criteria, the research sample is 26 companies in the Food and Beverage Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange starting in 2019-2022. In this research, the type of data used is quantitative data. The data source used in this research was obtained from the Indonesia Stock Exchange (BEI) website. The data collection method used in this research is documentation techniques. The documentation technique in this research was carried out by collecting secondary data in the form of research via the Indonesian Stock Exchange (BEI) via www.idx.co.id. The data analysis method uses multiple linear regression analysis with SPSS.25 Based on the results of the t test that has been carried out, it can be concluded that audit tenure has no effect on quality, audit rotation has no effect on audit quality, company size has no effect on audit quality. Based on the results of the F test, it was concluded that audit tenure, audit rotation, company size had a simultaneous positive and significant effect on audit quality